2010
DOI: 10.1093/cercor/bhq177
|View full text |Cite
|
Sign up to set email alerts
|

The Polysialylated Form of the Neural Cell Adhesion Molecule (PSA-NCAM) Is Expressed in a Subpopulation of Mature Cortical Interneurons Characterized by Reduced Structural Features and Connectivity

Abstract: Principal neurons in the adult cerebral cortex undergo synaptic, dendritic, and spine remodeling in response to different stimuli, and several reports have demonstrated that the polysialylated form of the neural cell adhesion molecule (PSA-NCAM) participates in these plastic processes. However, there is only limited information on the expression of this molecule on interneurons and on its role in the structural plasticity of these cells. We have found that PSA-NCAM is expressed in mature interneurons widely di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
81
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 56 publications
17
81
3
Order By: Relevance
“…NRCAM-PSA-expressing interneurons in mice show reduced dendritic spine numbers, decreased arborization, and changes in the synaptic connectivity (54). A study of cultured hippocampal neurons showed that PSA-NRCAM is required for N-methyl-D-aspartate (NMDA) receptor-dependent LTP and acts as an antagonist at N2RB-subunit-bearing NMDA receptors, preventing glutamate-induced cell death (55,56).…”
Section: Resultsmentioning
confidence: 99%
“…NRCAM-PSA-expressing interneurons in mice show reduced dendritic spine numbers, decreased arborization, and changes in the synaptic connectivity (54). A study of cultured hippocampal neurons showed that PSA-NRCAM is required for N-methyl-D-aspartate (NMDA) receptor-dependent LTP and acts as an antagonist at N2RB-subunit-bearing NMDA receptors, preventing glutamate-induced cell death (55,56).…”
Section: Resultsmentioning
confidence: 99%
“…The NCAM extracellular region can be modified by polysialylation (PSA-NCAM), which is implicated in mediating synaptic plasticity (33). PSA-NCAM is highly expressed in the embryonic and early postnatal stages and in interneuron populations in the mature cortex (33)(34)(35)(36). The 140-kDa isoform NCAM140 interacts physically and functionally with EphA3 to a greater extent than other isoforms (2) and is most prominent in axonal growth cones of developing neuronal cells (37).…”
Section: Neural Cell Adhesion Molecule (Ncam)mentioning
confidence: 99%
“…Interestingly, interneurons, as pyramidal neurons, in the mPFC also respond with structural changes to chronic stress, increasing their dendritic arborization (Gilabert-Juan et al, 2013). These changes in interneuronal structure may be mediated by the polysialylated form of the neural cell adhesion molecule (PSA-NCAM), which is exclusively expressed by interneurons in the mPFC of rodents (Gómez-Climent et al, 2011;Varea et al, 2005) and humans (Varea et al, 2007b). The expression of PSA-NCAM is regulated by chronic stress in the hippocampus (Pham et al, 2003;Sandi et al, 2001), the amygdala (Cordero et al, 2005), the piriform cortex (Nacher et al, 2004) and other cerebral regions (see (Sandi, 2004), for review).…”
Section: Introductionmentioning
confidence: 99%